THE MUSICAL-FOLKLORE LITERACY IN THE INITIAL CLASSES IN THE CONDITIONS OF A MULTIETHNIC ENVIRONMENT - Тодоров, Виталий; Великсар, Вероника (SWorldJournal, 2022)
Folklore is one of the most powerful means to help shape the musical culture of the new generation as it is genetically set in us. In the Taraklia region of Republic of Moldova, the population is multinational, and we take this into account. Of course, th